Senderización y señalética turística de los atractivos naturales Balneario Santa Fe y Cascadas Jabalí de la Parroquia Rural Progreso, Cantón Pasaje, Provincia de El Oro - Cuenca Herrera, Jessika Paola (2016)
During decades, tourism has experimented a continous employment and a deep diversification, until become into one of the best economic sectors wich grow up fastly in the world. The world tourism keep a strong relation with the development and a growing number of news destines register in it. This dinamic has converted the tourism in a motor of the socioeconomic progress. However there are alot of touristic places around the world who produce a few richness with litle prosperity and high social and environmental cost in this touristic activity. For a destination to achieve sustainable tourism development, it should aim to care for the environment, preserve the historical and cultural wealth and protect communities; Therefore, the Ministry of Tourism of Ecuador, in accordance with the “Ecuador Potencia Turística” he decided to design an integral structure signaling and common direction for domestic and foreign tourists, provide them with easy and efficient access to each destinations, in order to improve safety, information and travel time, allowing them to explore every attraction better. This search work proposes the Sederizacion and Touristic Señalética for the Natural Attractives balneario Santa Fe and Waterfalls Jabali of the rural parish Progreso, Canton Pasaje, Province of the Oro. The rural parish Progreso is ubicated i the Canton Pasaje, province of the Oro, in the south of the Ecuadorian coast between the geographic coordenadas 631.500 E y 634.00 O y 9632.00 N y 963.300 S. and it has a countless number of natural atractivs which attarct attention of the all kind of visitants. The Balneario Santa Fe and the waterfalls Jabali are localized in the Muyuyacu Community and it has a high natural, touristic an socioecomic value. To access to this atrtactives people should walk for a path which doesn´t has a right senderizacion to facility the access to the visitants. Also, this path doesn´t has the necessary studies to determine the capacity of the path and at the same time contribute to the sustainable tourism development of the place. With the aim of proposing possible solutions to the problematic pointed wing in this Project under study, arises the SEDERIZACION AND TOURISTIC SEÑALÉTICA FOR THE NATURAL ATTRACTIVES BALNEARIO SANTA FE AND WATERFALLS JABALI OF THE RURAL PARISH PROGRESO, CANTON PASAJE, PROVINCE OF THE ORO. During the development proces of this project it was carried out the achievement of three planted especific objectives, this objectives were: Perform a tourist diagnosis about the rural parish Progreso, Propose Senderización and Touristic Señaletica of the Natural Attractives Balneario Santa Fe and Waterfalls Jabalí; and identify the potential environmental impacts generated in the project phases To comply with the objective first specific was raised the tourist diagnosis for the rural parish Progreso, using the following methodology: the analytical and bibliographic method that allowed them to collect 5 information from the tourist attractions The observation technique, which was needed to move to the place of study to collect data of the attractions with the help of GPS, as well as to obtain a photographic record of the place. To comply with the first specific objective, about Propose Senderizacion and Touristic Señaletica for the Natural attractives Balneario Santa Fe and Waterfalls Jabali was applied the analytical, synthetic and descriptive method these allowed to obtain information and relevant analysis to establish the attractions of greater interest, also, this methodology allowed recollect the main points required and proceeding to trace the path in a geo-referential map of the site. To complete with the third especific objective about Identify the potential environmental impacts generated in the project phases, it was applied the Matriz de Causa y Efecto of the Leopold autor, this method allowed indentify the environmental impact wich would cause the implementation of the señaletica proposal to the path to the natural attractives Balneario Santa and waterfalls Jabali. Also, it was proposed a management plan with the purpose of prevent environmental impact during the project phases. Regarding the research results it can be mentioned that the diagnosis of the Parroquia San Pedro de Vilcabamba, which could be the location, boundaries, flora, fauna, tourist attractions, infrastructure and social aspects was performed. All this information was reflected in the records of the Ministry of Tourism, also gathering information based on the methodology of diagnosis Matrix author Carla Ricaurte Quijano was made, also was necessary relevant interview Engineer Maritza San Martín, President of the GAD of the Rural Parish Progreso, and Mr. Rubén Merchán, community guide of Muyuyacu site, this information helped reinforce the information of the current situation to investigate. It was also considered a design of signage with relevant information of the attractions to visit taking as reference the Manual Signaling Tourist 2011. Also it has been considered a porpuse about an Environmental Management Plan to prevent the possible environmental impacts that the project causes. Among the most important findings are that the parish does not have adequate infrastructure about to hotels and restaurants, the natural attractives Balneario Santa Fe and Waterfalls Jabalí, have unique natural beauty, however, actually they haven´t promote and support plans, which causes a lack at provincial and national level. It´s recommended that the competent authorities play a suitable tourism development plan of this natural attractions. Also it´s recommended to ejecute the present project about senderización y señalética turística of the Natural Attractivos Balneario santa Fe and Waterfalls Jabalí, which help care the flora and fauna of the place and provide better services to travelers.